Impact of Gender Role Attitudes and Gender Differences on the Evaluation of Female Leaders: Insights from a Survey of Japanese University Students - Muto, Mami; Katsurada, Emiko (Advances in Social Sciences Research Journal, 2024)
Women’s active participation in society is desirable. However, it has not increased sufficiently in contemporary Japan, where the ratio of women decision-makers in politics and corporations is low, and gender inequality persists. One reason for this could be people’s negative perception of female leaders. This study focused on female managers as female leaders. It examined whether people’s gender-role attitudes might affect their attitudes about female leaders and whether these attitudes might differ depending on people’s sex (males or females). We administered a collective-style questionnaire survey to university students (N=107, 46 men and 61 women, mean age=20.11, SD=1.04) in Japan. We adopted a three-way between-subjects survey design; gender-role attitudes (traditional or equal) x managers (male condition or female condition) x participants’ sex (male or female). The results indicated that the participants’ gender-role attitudes had a more substantial effect on evaluating female managers than the participants’ gender. People with liberal gender-role attitudes had a highly positive perception of female leaders, whereas those with traditional gender-role attitudes considered female leaders more strictly. The results of this study indicated that gender-role attitudes do not affect the assessment of male leaders, suggesting that individual values might not affect the evaluation of male leaders. In contrast, these variables affected the assessment of female leaders. Therefore, we concluded that gender-role attitudes are essential for promoting the psychological acceptance of women leaders, which suggests the need to develop personnel with egalitarian gender-role attitudes to increase and popularize women managers in Japanese society.